Increasing the pump current range of a single-frequency laser diode tuned to the caesium D2 line. (November 2021) - Bagaeva, O.O.; Ivanov, A.V.; Drozdovskii, V.N.; Kurnosov, V.D.; Kurnosov, K.V.; Romantsevich, V.I.; Simakov, V.A.; Chernov, R.V.
Abstract: It is shown experimentally and theoretically that increasing the pump current of a laser diode and simultaneously lowering its temperature can ensure an order of magnitude increase in the range of pump currents where the diode emission frequency is tuned to the caesium D2 line. The results are compared to the case where the laser diode and fibre Bragg grating temperatures are maintained constant and only the laser pump current is varied.